2011
DOI: 10.1038/nature10559
|View full text |Cite
|
Sign up to set email alerts
|

Spalt mediates an evolutionarily conserved switch to fibrillar muscle fate in insects

Abstract: Flying insects oscillate their wings at high frequencies of up to 1,000 Hz and produce large mechanical forces of 80 W per kilogram of muscle. They utilize a pair of perpendicularly oriented indirect flight muscles that contain fibrillar, stretch-activated myofibres. In contrast, all other, more slowly contracting, insect body muscles have a tubular muscle morphology. Here we identify the transcription factor Spalt major (Salm) as a master regulator of fibrillar flight muscle fate in Drosophila. salm is necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
183
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(186 citation statements)
references
References 35 publications
3
183
0
Order By: Relevance
“…4A,B,E), demonstrating that, even though the abdominal muscle pattern at 50 hours APF was completed (Bate et al, 1991), muscles sustain significant growth during late pupal development. Tubular muscles contain an internal lumen devoid of actin where nuclei are found (Peckham et al, 1990; Schönbauer et al, 2011). Our studies showed that the lumen was maintained constant in size along development (supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A,B,E), demonstrating that, even though the abdominal muscle pattern at 50 hours APF was completed (Bate et al, 1991), muscles sustain significant growth during late pupal development. Tubular muscles contain an internal lumen devoid of actin where nuclei are found (Peckham et al, 1990; Schönbauer et al, 2011). Our studies showed that the lumen was maintained constant in size along development (supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Morphologically, there are two major muscle types in the Drosophila adult: fibrillar muscles, which are present exclusively as indirect flight muscles, and tubular muscles, which include the jump, leg and abdominal muscles (Peckham et al, 1990; Schönbauer et al, 2011). In this work, we used the adult abdominal muscles as our model system to study adult myogenesis in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…with Mef2RNAi(15550) at 25°C, and could be linked to the different genetic programs in fibrillar and tubular muscle (Schonbauer et al, 2011).…”
Section: Research Reportmentioning
confidence: 99%
“…Importantly, recent evidence in the model organism, Drosophila, demonstrated a direct link between myonuclei positioning and proper muscle function, emphasizing the physiological significance of correct myonuclear positioning in proper movement of the organism. [7][8][9] Striated muscle fibers are multinucleated cells of variable size, morphology and physiology (e.g., fast or slow muscles), [10][11][12] but in each of the distinct muscle types, the nuclei, as well as other cytoplasmic organelles are evenly distributed along the entire cytoplasm, suggesting a mechanism capable of sensing muscle dimensions, which is coupled to the cellular machinery capable of moving and/or anchoring organelles within the cell. Surprisingly, information regarding such mechanisms is extremely limited, possibly due to the inability to follow the dynamics of organelle positioning within contracting muscles in live organisms.…”
Section: Positioning Nuclei Within the Cytoplasm Of Striated Muscle Fmentioning
confidence: 99%